Severe hypoglycaemia in 1076 adult patients with type 1 diabetes: influence of risk markers and selection. - Pedersen-Bjergaard, U; Pramming, S; Heller, SR; Wallace, T; Rasmussen, A; Jørgensen, H; Matthews, DR; Hougaard, P; Thorsteinsson, B (2004)
BACKGROUND: Differences between studies in rates of severe hypoglycaemia in type 1 diabetic cohorts are common and poorly understood. The purpose of this study was to assess the frequency of severe hypoglycaemia in unselected patients treated in different secondary care centres and to evaluate the influence of risk markers, clinical setting and selection. METHODS: Cross-sectional Danish-British multicentre survey of 1076 consecutive adult patients with clinical type 1 diabetes who completed a detailed questionnaire on hypoglycaemia and related issues. Key variable was the self-reported rate of severe hypoglycaemia during the preceding year. RESULTS: The overall rate of severe hypoglycaemia in the preceding year was 1.3 episodes/patient-year and episodes were reported by 36.7% of subjects. The distribution was highly skewed with 5% of subjects accounting for 54% of all episodes. There were no significant differences between countries or centres. Reduced hypoglycaemia awareness, peripheral neuropathy and smoking were the only significant risk markers of severe hypoglycaemia in a stepwise multivariate analysis. In a subgroup selected to be similar to the Diabetes Control and Complications Trial (DCCT) cohort, the rate of severe hypoglycaemia was 0.35 episodes/patient-year and only retinopathy was a significant risk marker together with state of awareness. CONCLUSION: Severe hypoglycaemia remains a significant clinical problem in type 1 diabetes. The rate of severe hypoglycaemia and the influence of risk markers are very sensitive to selection and differences in rates between centres or studies seem to disappear after correction for differences in clinical characteristics. Smoking is a novel overall risk marker of severe hypoglycaemia.